Coraline Connors, a catechism - Clark, Megan, author; Altschul, Andrew, advisor; Vara, Vauhini, committee member; Diffrient, Scott, committee member (Colorado State University. Libraries, 2024)
Below is the story of Coraline Connors, a sixteen-year-old Catholic, lesbian runaway. Coraline is mouthy, irreverent, and acerbic, but, above all else, Coraline is a lost kid looking for a place to belong. Told in first-person point of view, this novel follows Coraline's journey from her childhood home in rural Pennsylvania to the Cambridge, Massachusetts radio station in which she was conceived. This thesis is interested in girlhood, coming of age, queer identity, and religion—in particular how the latter two intersect. It is dedicated to all the real-world Coralines.